The Effect Of Paclobutrazol Concentration And Types Of Organic Liquid Fertilizer On The Growth And Production Of Tomató (Solanum Lycopersicum L.) - Adila Sukma Jayanti; Agus sulistyono; Didik Utomo Pribadi (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Tomatoes are a horticultural commodity that has the potential to be developed because it has high economic value and great export potential. The increase in tomato needs is often not offset by increased production so that Indonesia has not been able to meet the needs of national tomatoes, in addition to the issue of food quantity has shifted to the issue of food quality and food safety by using natural ingredients. This study aims to determine the concentration of paclobutrazol that can simulate reproductive growth and the best type of liquid organic fertilizer in replacing chemical fertilizers to increase the growth and yield of tomato plants. The combination of paclobutrazol concentration and liquid organic fertilizer is expected to increase tomato yield. This study used a plot design divided into two factors, namely the concentration of paclobutrazol and the type of liquid organic fertilizer with 16 combinations of treatments repeated 3 times. The first factor is the concentration of paclobutrazol with 4 levels, namely 0 ppm, 100 ppm, 150 ppm, and 200 ppm. The second factor is the type of liquid organic fertilizer with 4 levels of NPK fertilizer 25 grams / plant, water hyacinth 150 ml / plant, banana peel 150 ml/plant, and NASA 150 ml / plant. The results showed interactions in the total number of fruits per plant, the total fresh weight of fruit per plant, and the percentage of fruit sets. Paclobutrazol concentration of 100 ppm and the type of liquid organic fertilizer banana skin, 150 ml/ plant showed the highest yield in the number of fruits per harvest period (12 pieces), total fruit count per plant (63 pieces), fresh weight of fruit per harvest period (436.63 grams), total fresh fruit weight per plant (1815.80 grams), and percentage of fruit set (76.83%).